Dynamic properties of confined hydration layers. - Perkin, S; Goldberg, R; Chai, L; Kampf, N; Klein, J (2009)
Prompted by the recent discovery that water and aqueous monovalent Na+ solutions remain fluid-like when confined to films of a few molecular layers between mica surfaces,[Raviv et al., Nature, 2001, 413, 51-54; and Raviv and Klein, Science, 2002, 297, 1540-1543] we now extend the previous study by comparing the shear- and normal-force properties of 0.1 M Na+, Cs+ and Ni2+ salt solutions which demonstrate a diverse range of behaviours under confinement. In the case of hydrated Na+ we extend the previous study to higher pressures, up to approximately 10 atmospheres, and record similar fluidity of the hydration layers at these elevated pressures. Aqueous Cs+ films under confinement between mica sheets have been found to be unable to support an applied load--that is to say they do not demonstrate any hydration repulsion regime--as a result of their lower hydration energy [see Goldberg et al., Phys. Chem. Chem. Phys., 2008, 10, 4939-4945] which contrasts with the properties of Na+. We show that 0.1 M Ni2+ solution remains close to its bulk viscosity down to nanometre thin films, but does not demonstrate a hydration repulsion. By comparing the properties of this range of cations, with differing valency and hydration, we aim to examine the conditions under which ions serve as effective lubricants and what we call the 'hydration lubrication' mechanism.